PELAYANAN PUBLIK DI KANTOR KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG TAHUN 2012 - Kadis Pujo I; Priyatno Harindra H; Turtiantoro . (Journal of Politic and Government Studies, 2013)
In this study, researchers wanted to know about public service in east Ungaran subdistrict office Semarang district 2012. The study focused on the official subdistrict service to people east Ungaran. Public service demands excellent human resources that is human resources.In this study using quantitative research methods of descriptive research. This study analyses how public service in east Ungaran subdistrict office Semarang district 2012. The population of this research is people east Ungaran subdistrict and the sample in this research is 84 people. Sample technique that use is random sampling technique.The results showed that public service in east Ungaran office subdistrict was good enough. People was satisfied about work of east Ungaran official subdistrict.Kata Kunci : Public Service